1983
DOI: 10.1177/001316448304300410
|View full text |Cite
|
Sign up to set email alerts
|

A Generalizability Study of the Conners' Teacher Rating Scale-Revised

Abstract: The hyperactivity scale of the Conners' Teacher Rating Scale-Revised (CTRS-R) was investigated to compare teachers' use of this instrument to its use by independent classroom observers. Results of this study indicate that teacher ratings of children are highly stable over time. Independent observers agree with one another within an occasion both within a classroom and across classrooms; however, observations based on a one-hour period are not stable over time, but a composite score based on three occasions can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This may be due to multiple factors, including the fact that the scales are not completed at the same time (due to teacher schedules), there is limited contact or time to develop relationships between teacher and child, and the CTRS cognitive subscale assesses a slightly broader set of symptoms (academic performance) than just the ADHD symptom list. Previous studies also suggest that there is a low correlation between teachers' ratings and ratings made by trained classroom observers using the CTRS (Conger et al, 1983;Kazdin et al, 1983). This 200 comparison between patients with ADHD and controls was not possible.…”
Section: Discussionmentioning
confidence: 94%
“…This may be due to multiple factors, including the fact that the scales are not completed at the same time (due to teacher schedules), there is limited contact or time to develop relationships between teacher and child, and the CTRS cognitive subscale assesses a slightly broader set of symptoms (academic performance) than just the ADHD symptom list. Previous studies also suggest that there is a low correlation between teachers' ratings and ratings made by trained classroom observers using the CTRS (Conger et al, 1983;Kazdin et al, 1983). This 200 comparison between patients with ADHD and controls was not possible.…”
Section: Discussionmentioning
confidence: 94%
“…Although the scale does not directly measure physiological stress responses, the subscales evaluate behaviors that are often associated with stress. The scale has high reliability (Conger, Conger, Wallander, Ward, & Dygdon, 1983) and agreement between raters (teacher and an observer) is also good (g = 0.70). In a previous study of 320 children, the revised scale (Conners et al, 1998) demonstrated hightest-retest reliability (n = 50; r = 0.86) and the sensitivity is 78% and specificity 91% for identifying children with ADHD.…”
Section: Semi-structured Interviews With Classroom Teachermentioning
confidence: 96%
“…-The Conners' Teacher Rating Scale was assessed in a generalizability study by Conger, Conger, Wallander, Ward, & Dygdon (1983). In one of their designs, teachers filled out the form on a sample of children on three occasions.…”
Section: Purposementioning
confidence: 99%